1999
DOI: 10.1002/(sici)1099-1255(199901/02)14:1<27::aid-jae490>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Unit roots in the presence of abrupt governmental interventions with an application to Brazilian data

Abstract: Unit roots in the presence of abrupt governmental interventions with an application to Brazilian data Texto para discussão, No. 349

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
0
17

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 9 publications
6
30
0
17
Order By: Relevance
“…This paper addresses the issue of measuring the degree of inertia in inflation in the presence of potential 'inliers'. It shows that by using robust unit root tests one reaches the same inference on the order of integration of the series as what is revealed by the modified procedure proposed by Cati et al (1999). The results also suggest that, contrary to previous findings, the degree of inertia in inflation is rather small.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…This paper addresses the issue of measuring the degree of inertia in inflation in the presence of potential 'inliers'. It shows that by using robust unit root tests one reaches the same inference on the order of integration of the series as what is revealed by the modified procedure proposed by Cati et al (1999). The results also suggest that, contrary to previous findings, the degree of inertia in inflation is rather small.…”
supporting
confidence: 57%
“…Durevall (1998), using an error correction formulation, found the level of inflation inertia in Brazil to be 0.41. Cati et al (1999) have argued that nearly all of the so-called shock plans which were designed to curb inflation and were implemented in Brazil since the mid-1980s brought inflation down for a few months and then failed.The observations corresponding to these months when inflation was artificially low have been termed 'inliers', and the authors have claimed that they tend to bias traditional unit root tests. This motivated them to design corrected tests by adding dummy variables to the usual augmented DickeyFuller (ADF) test.…”
Section: The Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Cati et al (1999) have constructed a test for series with this kind of break with an application to the inflation rate in Brazil for 1974:01 to 1993:06. They have found mixed results, but have concluded that we cannot reject the unit root hypothesis.…”
Section: Methodsmentioning
confidence: 99%
“…Para isso foi aplicado o teste Kwiatkowski-Phillips-Schmidt-Shin (KPSS). A vantagem desse teste resulta do baixo poder de testes convencionais, que tendem a não rejeitar a hipótese nula demasiadas vezes (Franses & Haldrup 1994, Cati et al 1999. Ademais, Kwiatkowski et al (1992) argumentam que o teste KPSS pode distinguir séries que aparentam ser estacionárias, séries que aparentam ter uma raiz unitária e séries para as quais os dados não são suficientemente informativos para ter a certeza se são estacionárias ou in-tegradas -como é o caso de séries com curta periodicidade (os resultados do teste estão na Tabela A.1 do Apêndice).…”
Section: Figura 2: Evolução Das Principais Variáveisunclassified